Apremilast for the treatment of palmo‐plantar non‐pustular psoriasis: A real‐life single‐center retrospective study. Issue 2 (26th December 2021) - Pavia, Giulia; Gargiulo, Luigi; Cortese, Andrea; Valenti, Mario; Sanna, Federica; Borroni, Riccardo G.; Costanzo, Antonio; Narcisi, Alessandra
Abstract: Palmoplantar psoriasis (PP) is a type of psoriasis that involves the skin of the palms and soles and can present as hyperkeratotic, similar to the vulgaris psoriasis of the body. Apremilast, as an oral inhibitor of phosphodiesterase 4 (PDE4), is currently approved for the treatment of psoriatic arthritis and for moderate‐to‐severe psoriasis in adult patients who have not responded or have contraindications or do not tolerate other systemic treatments. We evaluated the efficacy and safety of apremilast in the treatment of non‐pustular palmo‐plantar psoriasis in a cohort of 12 patients. We found a clinical response of clear/almost clear palmoplantar psoriasis (PPPGA score 0/1) in 83.33% of our patients, at week 16. No significant safety issues were reported and none of our patients had to discontinue the drug.